A process for preparing D-tagatose crystals
By using ultrasonic assisted crystal cultivation and adding materials while evaporating and concentrating, combined with hydroxypropyl methyl cellulose and infrared spectrum control, high purity, high yield, and shape rules were successfully prepared. The D-tagsose crystals solve the problems of unstable quality and limited application when preparing D-tagsose crystals in the prior art.
Patent Information
- Application Number
- CN202411480010.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-23
AI Technical Summary
In the prior art, there are problems such as agglomeration, impurities mixing, explosive crystals, small crystals, low yield per tank and uneven distribution of crystal mesh when preparing D-tags crystals, resulting in limited application and unstable quality. .
Ultrasonic assisted in the cultivation of crystals in saturated D-tag sugar solution, and the crystal growth is controlled by evaporation and concentration while adding materials while flowing. Hydroxypropyl methyl cellulose is added to reduce viscosity, and infrared spectroscopy is used to monitor concentration changes to control supersaturation. The regular D-tags crystals were finally obtained by filtration and ethanol flow addition.
D-tagsose crystals with regular shape, uniform particle size, purity above 99.5%, and yield above 60% were prepared, avoiding the problems of agglomeration and impurities mixing, and improving the fluidity and added value of the product.
Smart Images

Figure CN118994271B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of industrial crystallization, and particularly relates to a process for preparing D-tagatose crystals. Background Art
[0002] D-Tagatose is a natural monosaccharide with a molecular formula of C6H 12 O6 is a diastereomer of fructose in structure. The sweetness of D-tagatose is similar to that of sucrose, about 92% of the sweetness of sucrose, but its energy is much lower than sucrose, about 1.5 kcal / g. D-tagatose is not only a better sweetener and filler for low-energy foods, but also has multiple functional properties such as preventing dental caries, preventing obesity, lowering blood sugar and improving intestinal flora. It is widely used in baked goods, beverages, dairy products, candies and other foods.
[0003] At present, the D-tagatose products on the market are mainly powdered solids, but solid powders usually have disadvantages such as easy agglomeration and easy mixing of impurities, which limits its application scenarios. Larger D-tagatose crystals are not only less likely to agglomerate, but also facilitate the separation of crystals and mother liquor during the crystallization process, reducing losses in the washing stage. Tagatose crystals with better crystal morphology also have higher added value.
[0004] In the prior art, D-tagatose solution is generally used for crystallization to obtain D-tagatose. However, D-tagatose solution with a high concentration (concentration > 80%) has a high viscosity and a high degree of supersaturation, which can easily cause adverse effects such as crystal explosion, small crystals, low single-pot yield, and uneven crystal size distribution during the crystallization process.
[0005] Therefore, finding a D-tagatose preparation process with simple process, low cost, good crystal quality and suitable for food industry production remains an urgent problem to be solved. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a process for preparing D-tagatose crystals. The crystals obtained by the process of the present invention have regular shapes, high product yield, good quality and good fluidity.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] A process for preparing D-tagatose crystals, specifically comprising the following steps:
[0009] (1) adding a seed solution to a saturated D-tagatose solution under the assistance of ultrasound, and then growing the crystals at 50-60° C., wherein the crystal growing process adopts simultaneous evaporation and concentration while adding materials;
[0010] (2) adding hydroxypropyl methylcellulose to the D-tagatose solution obtained in step (1), and then cooling and crystallizing the solution under infrared spectroscopy;
[0011] (3) After filtering the D-tagatose solution obtained in step (2), a first filter residue and a filtrate are obtained, ethanol is added to the filtrate to continue crystallization, and then centrifuged to obtain a second filter residue, wherein the first filter residue and the second filter residue are D-tagatose crystals.
[0012] The crystals obtained by the present invention are single crystals with regular shapes, wherein the mass fraction of 20-40 mesh crystals accounts for more than 80%, the crystal purity is greater than 99.5%, and the product yield is greater than 60%.
[0013] Preferably, the method for preparing the saturated D-tagatose solution in step (1) is: adding an antioxidant to the D-tagatose solution and evaporating and concentrating the solution to a saturated solution.
[0014] Preferably, the concentration of the D-tagatose solution is 50-60% and the purity is 88-95%;
[0015] The antioxidant is at least one of ascorbyl palmitate and tocopherol polyethylene glycol succinate;
[0016] The added amount of the antioxidant is 0.01-0.05% of the mass of the D-tagatose solution.
[0017] Preferably, the power of the ultrasound in step (1) is 100-150W;
[0018] The seed solution is a seed ethanol solution, wherein the mass ratio of the seed to anhydrous ethanol is 1:1-2, and the seed is 100-150 mesh; while the ethanol solution is used to facilitate the introduction of the seed, the dispersibility of the seed can be increased and the adhesion between the seed can be reduced;
[0019] The amount of seed crystal added is 1-3% of the mass of D-tagatose;
[0020] The crystal growing time is 10-14h, and the stirring rate is 150-300rpm;
[0021] The temperature of the saturated D-tagatose solution is 50-60°C.
[0022] Preferably, the crystal solution in step (1) is added by bottom compressed gas, and the stirring rate of the saturated D-tagatose solution is 400-500 rpm;
[0023] Wherein, the compressed gas is any one of air, carbon dioxide, nitrogen, helium and argon;
[0024] The pressure of the compressed gas is 0.3-1.2 MPa.
[0025] Preferably, the steam pressure of the evaporation in step (1) is 150-200 kPa, the rate of the material addition is 0.2-0.5 L / h, and the material is a D-tagatose solution with a concentration of 50-60%.
[0026] The principle of the evaporation and concentration while adding materials adopted by the present invention is mainly to gradually increase the solute concentration in the solution to reach a supersaturated state by continuously evaporating the solvent, thereby promoting the precipitation and growth of crystals; at the same time, continuously adding new materials can replenish the solute in the solution, maintain the stability and concentration balance of the solution, and avoid excessive evaporation causing the solution concentration to be too high, thereby affecting the quality and growth rate of the crystals.
[0027] Preferably, the amount of hydroxypropyl methylcellulose added in step (2) is 0.05-0.2% of the mass of the sugar solution;
[0028] The specific process of using the infrared spectrum is: tracking the concentration change of D-tagatose at the infrared spectrum absorption peak of 1020cm-1, continuously collecting the infrared spectrum every 23s, the supersaturation is 1.05-1.20, and the supersaturation is controlled by controlling the cooling water temperature, and the temperature difference between the cooling water and the sugar solution is 3-5°C;
[0029] The temperature is lowered to 15-20°C.
[0030] Preferably, the cooling rate is: 0.3-0.5°C per hour in the range of 60-55°C; 0.5-0.8°C per hour in the range of 55-40°C; 0.8-1.0°C per hour in the range of 40-25°C; 1.0-1.2°C per hour in the range of 25-15°C.
[0031] Preferably, the filtration in step (3) uses a sieve with a mesh size of 40-60.
[0032] Preferably, the amount of ethanol added in step (3) is 3-5 times the volume of the filtrate, the flow acceleration is 0.1-0.2 L / h, and the crystallization time is 1-2 h;
[0033] The stirring rate of the crystallization is 100-300 rpm.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] (1) In the process of the present invention, the addition of antioxidants can not only reduce the Maillard reaction and increase the whiteness of the product, but also act as a surfactant to improve the uniformity of the crystals, and at the same time can modify the crystal form and increase the fluidity and packing density of the crystals;
[0036] (2) The process of the present invention can dissolve small crystals attached to the surface of large seed crystals with the assistance of ultrasonic waves, and combined with the method of introducing compressed gas from the bottom, it can improve the uniformity of crystallization and the strength of the crystal;
[0037] (3) In the process of the present invention, adding hydroxypropyl methylcellulose to the sugar solution can reduce the viscosity of the sugar solution, accelerate crystal growth, and avoid explosive nucleation;
[0038] (4) The process of the present invention uses low-temperature crystal growth and infrared spectroscopy to monitor concentration changes in real time to control supersaturation, thereby shortening the crystallization cycle, and the product has high purity and stable quality;
[0039] (5) The present invention can control the crystal growth rate by adding materials while evaporating and concentrating. By accurately controlling the evaporation and addition rates, the concentration change of the solution can be adjusted, thereby achieving effective control of the crystal growth rate; maintaining the stability of the solution, the addition of materials can replenish the solute in the solution in time, and prevent the instability caused by excessive concentration of the solution due to evaporation, such as too fast crystallization, generation of impurities, etc.; improving the quality of the crystal, uniform concentration changes and stable solution environment are conducive to the formation of crystals with regular shape and uniform size. High-quality crystals are more stable in physical and chemical properties, and have better performance and application value;
[0040] (6) After the large crystals are intercepted by the screen, the process of the present invention uses the small crystals in the mother liquor as seeds and adds ethanol to continue crystallization, which can improve the yield of the crystals and shorten the centrifugation and drying time;
[0041] (7) The D-tagatose crystals obtained by the process of the present invention have uniform particle size, more than 80wt% of the crystals have a mesh size of 20-40, the crystal purity is more than 99.5%, the crystal morphology is good, and it is not easy to aggregate. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0043] Figure 1 This is a picture of the D-tagatose crystal product obtained in Example 1 of the present invention;
[0044] Figure 2 This is a picture of the D-tagatose crystal product obtained in Comparative Example 1. DETAILED DESCRIPTION
[0045] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] Example 1
[0047] A process for preparing D-tagatose crystals comprises the following specific steps:
[0048] (1) adding 0.05 wt % ascorbyl palmitate to a D-tagatose solution having a concentration of 50% and a purity of 95%, and evaporating and concentrating the solution to a saturated D-tagatose solution at 50° C.;
[0049] The crushed 100-120 mesh crystals are added into ethanol (the mass ratio of ethanol to crystals is 1:1) to obtain a seed solution;
[0050] (2) Under the assistance of 100W ultrasonic wave, at 0.3MPa, seed solution was added by bottom compressed air at 500rpm to stimulate crystallization, and the amount of seed added was 1% of the mass of D-tagatose; then, at 150KPa, the material was added while evaporating and concentrating at a flow rate of 0.2L / h to grow the crystal, and the crystal was grown at 50℃ and 150rpm for 12h; the material was D-tagatose solution with a concentration of 50% and a purity of 95%;
[0051] (3) adding 0.05 wt% hydroxypropyl methylcellulose to the D-tagatose solution obtained in step (2), and then cooling the crystallized syrup to 15° C. at a supersaturation of 1.2 under infrared spectroscopy;
[0052] The specific process of using infrared spectroscopy is as follows: when the infrared spectrum absorption peak is 1020cm -1 The concentration change of D-tagatose was tracked at 1.20, and the infrared spectrum was collected continuously every 23 seconds. The supersaturation was controlled by controlling the cooling water temperature. The temperature difference between cooling water and sugar solution was 3-5℃.
[0053] The cooling rate is: 0.3-0.5°C per hour in 60-55°C, 0.5-0.8°C per hour in 55-40°C, 0.8-1.0°C per hour in 40-25°C, 1.0-1.2°C per hour in 25-15°C, and the crystallization period is 55h;
[0054] (4) The D-tagatose solution obtained by cooling the temperature in step (3) is intercepted by a 60-mesh screen to obtain a first filter residue and a filtrate. The filtrate is stirred at 100 rpm and 5 times ethanol is added to the filtrate at a flow rate of 0.2 L / h while stirring to continue crystallization. After the addition of ethanol, the crystallization is continued by stirring for 2 h, and then centrifuged and dried to obtain a second filter residue. The first filter residue and the second filter residue are D-tagatose crystals. The relevant product is shown in the figure below. Figure 1 ;
[0055] The D-tagatose crystals prepared in this example have uniform particle size, more than 83.25wt% of the crystals have a mesh size of 20-40, the crystal morphology is good, and it is not easy to agglomerate; the D-tagatose crystal yield is 60.35%, the crystal purity is 99.68%, the whiteness is 95.2%, the bulk density is 0.85g / mL, the angle of repose is 35°, and the obtained crystal particle size distribution is shown in Table 1.
[0056] Table 1 Crystalline particle size distribution of Example 1
[0057]
[0058] Example 2
[0059] A process for preparing D-tagatose crystals comprises the following specific steps:
[0060] (1) adding 0.01 wt % ascorbyl palmitate and 0.01 wt % tocopherol polyethylene glycol succinate to a D-tagatose solution having a concentration of 60% and a purity of 88%, and evaporating and concentrating the solution to a saturated D-tagatose solution at 60° C.;
[0061] Add the crushed 100-150 mesh crystals into ethanol (the mass ratio of ethanol to crystals is 2:1) to obtain a seed solution;
[0062] (2) Under the assistance of 140W ultrasonic wave, under 1.0MPa, seed solution was added by bottom compressed carbon dioxide to stimulate crystallization with stirring at 500rpm, and the amount of seed solution added was 3% of the mass of D-tagatose; then, under 180KPa, evaporation and concentration were performed while adding materials at a flow rate of 0.3L / h, and crystallization was performed at 60℃ and 300rpm for 10h;
[0063] (3) adding 0.2 wt % hydroxypropyl methylcellulose to the D-tagatose solution obtained in step (2), and then cooling the crystallized syrup to 20° C. at a supersaturation of 1.05 under infrared spectroscopy;
[0064] The specific process of using infrared spectroscopy is as follows: when the infrared spectrum absorption peak is 1020cm -1The concentration change of D-tagatose was tracked, and the infrared spectrum was continuously collected every 23 seconds. The supersaturation was 1.05. The supersaturation was controlled by controlling the cooling water temperature. The temperature difference between cooling water and sugar solution was 3-5℃.
[0065] The cooling rate is: 0.3-0.5°C per hour within 60-55°C, 0.5-0.8°C per hour within 55-40°C, 0.8-1.0°C per hour within 40-25°C, 1.0-1.2°C per hour within 25-20°C, and the crystallization period is 65h;
[0066] (4) The D-tagatose solution obtained by cooling the temperature in step (3) is intercepted by a 40-mesh sieve to obtain a first filter residue and a filtrate. The filtrate is stirred at 200 rpm, and 3 times ethanol is added to the filtrate at a flow rate of 0.1 L / h while stirring to continue crystallization. After the addition of ethanol is completed, the crystallization is continued for 1 hour, and then centrifuged and dried to obtain a second filter residue. The first filter residue and the second filter residue are D-tagatose crystals;
[0067] The D-tagatose crystals prepared in this example have uniform particle size, more than 83.15wt% of the crystals have a mesh size of 20-40, the crystal morphology is good, and it is not easy to agglomerate; the D-tagatose crystal yield is 64.34%, the crystal purity is 99.78%, the whiteness is 94.3%, the bulk density is 0.86g / mL, the angle of repose is 35°, and the obtained crystal particle size distribution is shown in Table 2.
[0068] Table 2 Crystalline particle size distribution of Example 2
[0069]
[0070] Example 3
[0071] A process for preparing D-tagatose crystals comprises the following specific steps:
[0072] (1) adding 0.01 wt % tocopherol polyethylene glycol succinate to a D-tagatose solution having a concentration of 55% and a purity of 92%, and evaporating and concentrating the solution to a saturated D-tagatose solution at 58° C.;
[0073] The crushed 100-150 mesh crystals were added into ethanol (the mass ratio of ethanol to crystals was 1.5:1) to obtain a seed solution;
[0074] (2) Under the assistance of 150W ultrasonic wave, compressed nitrogen was introduced from the bottom at 1.2MPa, and seed solution was added at 400rpm to stimulate crystallization. The amount of seed solution added was 2% of the mass of D-tagatose. Then, at 200KPa, the material was added while evaporating and concentrating at a flow rate of 0.5L / h to grow the crystal. The crystal was grown at 58℃ and 300rpm for 14h.
[0075] (3) adding 0.1 wt% hydroxypropyl methylcellulose to the D-tagatose solution obtained in step (2), and then cooling the crystallized syrup to 18° C. at a supersaturation of 1.10 under infrared spectroscopy;
[0076] The specific process of using infrared spectroscopy is as follows: when the infrared spectrum absorption peak is 1020cm -1 The concentration of D-tagatose was tracked at 1.10, and the infrared spectrum was collected continuously every 23 seconds. The supersaturation was controlled by controlling the cooling water temperature. The temperature difference between the cooling water and the sugar solution was 3-5°C.
[0077] The cooling rate is: 0.3-0.5°C per hour within 58-55°C, 0.5-0.8°C per hour within 55-40°C, 0.8-1.0°C per hour within 40-25°C, 1.0-1.2°C per hour within 25-18°C, and the crystallization period is 57h;
[0078] (4) The D-tagatose solution obtained by cooling the temperature in step (3) is intercepted by a 50-mesh sieve to obtain a first filter residue and a filtrate. The filtrate is stirred at 300 rpm, and 4 times ethanol is added to the filtrate at a flow rate of 0.15 L / h while stirring to continue crystallization. After the addition of ethanol is completed, the crystallization is continued for 1.5 hours, and then centrifuged and dried to obtain a second filter residue. The first filter residue and the second filter residue are D-tagatose crystals;
[0079] The D-tagatose crystals prepared in this example have uniform particle size, more than 80.74wt% of the crystals have a mesh size of 20-40 mesh, the crystal morphology is better, and it is not easy to agglomerate; the D-tagatose crystal yield is 62.12%, the crystal purity is 99.75%, the whiteness is 94.6%, the bulk density is 0.84g / mL, the angle of repose is 34°, and the obtained crystal particle size distribution is shown in Table 3.
[0080] Table 3 Crystalline particle size distribution of Example 3
[0081]
[0082] Example 4
[0083] A process for preparing D-tagatose crystals comprises the following specific steps:
[0084] (1) adding 0.03 wt % ascorbyl palmitate to a D-tagatose solution having a concentration of 58% and a purity of 95%, and evaporating and concentrating the solution to a saturated D-tagatose solution at 56° C.;
[0085] The crushed 120-140 mesh crystals were added into ethanol (the mass ratio of ethanol to crystals was 1.8:1) to obtain a seed solution;
[0086] (2) Under the assistance of 120W ultrasonic wave, at 1.0MPa, seed solution was added by introducing compressed helium from the bottom, stirring at 480rpm to stimulate crystallization, and the amount of seed solution added was 1.5% of the mass of D-tagatose; then, at 160KPa, evaporation and concentration were performed while adding materials at a flow rate of 0.3L / h, and crystals were grown at 56℃ and 300rpm for 13h;
[0087] (3) adding 0.1 wt% hydroxypropyl methylcellulose to the D-tagatose solution obtained in step (2), and then cooling the crystallized syrup to 16° C. at a supersaturation of 1.05 under infrared spectroscopy;
[0088] The specific process of using infrared spectroscopy is as follows: when the infrared spectrum absorption peak is 1020cm -1 The concentration change of D-tagatose was tracked, and the infrared spectrum was continuously collected every 23 seconds. The supersaturation was 1.05. The supersaturation was controlled by controlling the cooling water temperature. The temperature difference between cooling water and sugar solution was 3-5℃.
[0089] The cooling rate is: 0.3-0.5°C per hour within 56-55°C, 0.5-0.8°C per hour within 55-40°C, 0.8-1.0°C per hour within 40-25°C, 1.0-1.2°C per hour within 25-16°C, and the crystallization period is 60h;
[0090] (4) The D-tagatose solution obtained by cooling the temperature in step (3) is intercepted by a 40-mesh sieve to obtain a first filter residue and a filtrate. The filtrate is stirred at 150 rpm, and 4 times ethanol is added to the filtrate at a flow rate of 0.15 L / h while stirring to continue crystallization. After the addition of ethanol is completed, the crystallization is continued for 1 hour, and then centrifuged and dried to obtain a second filter residue. The first filter residue and the second filter residue are D-tagatose crystals;
[0091] The D-tagatose crystals prepared in this example have uniform particle size, more than 81.03wt% of the crystals have a mesh size of 20-40, the crystal morphology is good, and it is not easy to agglomerate; the D-tagatose crystal yield is 62.37%, the crystal purity is 99.76%, the whiteness is 94.7%, the bulk density is 0.84g / mL, the angle of repose is 34°, and the obtained crystal particle size distribution is shown in Table 4.
[0092] Table 4 Crystalline particle size distribution of Example 4
[0093]
[0094] Example 5
[0095] A process for preparing D-tagatose crystals comprises the following specific steps:
[0096] (1) adding 0.02 wt % tocopherol polyethylene glycol succinate to a D-tagatose solution having a concentration of 55% and a purity of 90%, and evaporating and concentrating the solution to a saturated D-tagatose solution at 60° C.;
[0097] Add the crushed 140-150 mesh crystals into ethanol (the mass ratio of ethanol to crystals is 2:1) to obtain a seed solution;
[0098] (2) Under the assistance of 150W ultrasonic wave, at 0.8MPa, seed solution was added by introducing compressed argon gas from the bottom and stirring at 450rpm to stimulate crystallization. The amount of seed solution added was 1% of the mass of D-tagatose. Then, at 180KPa, the material was added while evaporating and concentrating at a flow rate of 0.4L / h to grow the crystal. The crystal was grown at 60℃ and 150rpm for 12h.
[0099] (3) adding 0.15 wt % hydroxypropyl methylcellulose to the D-tagatose solution obtained in step (2), and then cooling the crystallized syrup to 18° C. at a supersaturation of 1.10 under infrared spectroscopy;
[0100] The specific process of using infrared spectroscopy is as follows: when the infrared spectrum absorption peak is 1020cm -1 The concentration of D-tagatose was tracked at 1.10, and the infrared spectrum was collected continuously every 23 seconds. The supersaturation was controlled by controlling the cooling water temperature. The temperature difference between the cooling water and the sugar solution was 3-5°C.
[0101] The cooling rate is: within 60-55°C, 0.3-0.5°C per hour, within 55-40°C, 0.5-0.8°C per hour, within 40-25°C, 0.8-1.0°C per hour, within 25-18°C, 1.0-1.2°C per hour, and the crystallization period is 61h;
[0102] (4) The D-tagatose solution obtained by cooling the temperature in step (3) is intercepted by a 50-mesh sieve to obtain a first filter residue and a filtrate. The filtrate is stirred at 220 rpm, and 3 times ethanol is added to the filtrate at a flow rate of 0.1 L / h while stirring to continue crystallization. After the addition of ethanol is completed, the crystallization is continued for 1 hour, and then centrifuged and dried to obtain a second filter residue. The first filter residue and the second filter residue are D-tagatose crystals;
[0103] The D-tagatose crystals prepared in this example have uniform particle size, more than 82.37wt% of the crystals have a mesh size of 20-40, the crystal morphology is good, and it is not easy to agglomerate; the D-tagatose crystal yield is 64.54%, the crystal purity is 99.81%, the whiteness is 94.9%, the bulk density is 0.86g / mL, the angle of repose is 32°, and the obtained crystal particle size distribution is shown in Table 5.
[0104] Table 5 Crystalline particle size distribution of Example 5
[0105]
[0106] Comparative Example 1
[0107] A process for preparing D-tagatose crystals comprises the following specific steps:
[0108] (1) Take a D-tagatose solution with a concentration of 50% and a purity of 95% and evaporate and concentrate it to a saturated D-tagatose solution at 60°C;
[0109] (2) Add 1.0wt% 100-120 mesh seed crystals to the saturated D-tagatose solution under stirring at 500rpm to stimulate crystallization, and grow the crystals for 3h; then cool down to 15℃ (cooling crystallization cycle is 76h) at a rate of 0.3℃ per hour within 60-55℃, 0.5℃ per hour within 55-40℃, 0.8℃ per hour within 40-25℃, and 1.0℃ per hour within 25-15℃ to obtain D-tagatose crystals after centrifugation and drying. The relevant product is shown in the figure. Figure 2 .
[0110] After the crystallization, the particle size distribution of D-tagatose crystals was uneven, 43.5wt% of the crystals had a mesh size of 20-40, the product yield was 44.34%, the purity was 98.17%, the whiteness was 87.6%, the bulk density was 0.67g / mL, the angle of repose was 45°, and the obtained crystal particle size distribution was shown in Table 6.
[0111] Table 6 Crystalline particle size distribution of Comparative Example 1
[0112]
[0113] It can be seen from the table that when the crystallization process of the present invention is not used, the crystal yield is low, the crystallization cycle is long, the crystals are small and the distribution range is wide, the whiteness is slightly low, the packing density is low, the crystal repose angle is large, and the fluidity is slightly poor.
[0114] Comparative Example 2
[0115] D-tagatose crystals were prepared according to the process of Example 1, which differed from Example 1 in that no antioxidant was added, and the remaining steps were the same as those of Example 1. After the crystallization, the particle size distribution of D-tagatose crystals was uneven, and 72.50wt% of the crystals had a mesh size of 20-40 mesh. The product yield was 56.21%, the purity was 98.46%, the whiteness was 89.1%, the bulk density was 0.76 g / mL, the angle of repose was 41°, and the particle size distribution of the obtained crystals was shown in Table 7.
[0116] Table 7 Crystalline particle size distribution of Comparative Example 2
[0117]
[0118] It can be seen from the table that adding antioxidants can reduce the Maillard reaction, increase the whiteness of the product, and at the same time improve the uniformity of the crystals, increase the crystallization yield, and increase the fluidity and packing density of the crystals.
[0119] Comparative Example 3
[0120] D-tagatose crystals were prepared according to the process of Example 2. The difference from Example 2 was that the seed solution was not added by the method of ultrasonic assistance combined with bottom compressed gas. The remaining steps were the same as Example 2. After the crystallization, the particle size distribution of D-tagatose crystals was uneven, and more than 72.14wt% of the crystals had a mesh size of 20-40 mesh. The product yield was 60.73%, the crystal purity was 99.03%, the whiteness was 90.8%, the bulk density was 0.76g / mL, the angle of repose was 41°, and the particle size distribution of the obtained crystals was shown in Table 8.
[0121] Table 8 Crystalline particle size distribution of Comparative Example 3
[0122]
[0123] It can be seen from the table that adding crystal seeds by combining ultrasonic assistance with bottom compressed gas can increase the uniformity of the crystals, and the crystal packing density is large and the fluidity is good.
[0124] Comparative Example 4
[0125] D-tagatose crystals were prepared according to the process of Example 2. The difference from Example 2 was that: instead of adding seed crystals by ultrasonic assistance combined with bottom compressed gas, crushed crystals were directly added. The remaining steps were the same as those of Example 2. After the crystallization, the particle size distribution of D-tagatose crystals was uneven, and more than 70.03wt% of the crystals had a mesh size of 20-40. The product yield was 60.52%, the crystal purity was 99.02%, the whiteness was 90.6%, the bulk density was 0.74g / mL, the angle of repose was 41°, and the particle size distribution of the obtained crystals was shown in Table 8.
[0126] Table 9 Crystalline particle size distribution of Comparative Example 4
[0127]
[0128] As can be seen from the table, by dissolving the seed crystals in ethanol and adding them, it is convenient to bring them in, and the dispersion of the seed crystals can be increased, the adhesion between the seed crystals can be reduced, and the crystals can be larger.
[0129] Comparative Example 5
[0130] D-tagatose crystals were prepared according to the process of Example 3, which differed from Example 3 in that hydroxypropyl methylcellulose was not added, and the remaining steps were the same as those of Example 3. After the crystallization, the particle size distribution of D-tagatose crystals was uneven, and more than 70.82wt% of the crystals had a mesh size of 20-40 mesh, the yield was 57.69%, the crystal purity was 98.83%, the whiteness was 90.3%, the bulk density was 0.76 g / mL, the angle of repose was 40°, and the particle size distribution of the obtained crystals was shown in Table 9.
[0131] Table 10 Crystalline particle size distribution of Comparative Example 5
[0132]
[0133] It can be seen from the table that after adding hydroxypropyl methylcellulose, at the same cooling rate, the explosive nucleation caused by high viscosity can be avoided, the yield is higher, and the crystals are larger.
[0134] Comparative Example 6
[0135] D-tagatose crystals were prepared according to the process of Example 4, which differed from Example 4 in that: instead of controlling supersaturation by cooling and crystallizing under the action of infrared spectroscopy, the temperature was cooled and crystallized to 18°C at a rate of 0.3°C per hour within 60-55°C, 0.5°C per hour within 55-40°C, 0.8°C per hour within 40-25°C, and 1.0°C per hour within 25-18°C (the cooling and crystallization cycle was 73h). The remaining steps were the same as those of Example 4. After the crystallization, the particle size distribution of D-tagatose crystals was uneven, and more than 50.39wt% of the crystals had a mesh size of 20-40. The yield of D-tagatose crystals was 42.95%, the crystal purity was 98.61%, the whiteness was 90.8%, the bulk density was 0.70g / mL, the angle of repose was 42°, and the particle size distribution of the obtained crystals was as shown in Table 10.
[0136] Table 11 Crystalline particle size distribution of Comparative Example 6
[0137]
[0138] It can be seen from the table that when the supersaturation is not controlled under the action of infrared spectroscopy, the temperature is cooled at a fixed cooling rate, the crystallization cycle is longer and the purity of the product is slightly lower.
[0139] Comparative Example 7
[0140] D-tagatose crystals were prepared according to the process of Example 5, which differed from Example 5 in that ethanol was not added and the product was directly centrifuged and dried. The remaining steps were the same as those of Example 5. After the crystallization, the uniformity of the particle size of the D-tagatose crystals was slightly poor, and more than 72.18wt% of the crystals had a mesh size of 20-40 mesh. The yield was 44.03%, the crystal purity was 98.84%, the whiteness was 91.3%, the bulk density was 0.77 g / mL, the angle of repose was 38°, and the particle size distribution of the obtained crystals was shown in Table 11.
[0141] Table 12 Crystalline particle size distribution of Comparative Example 7
[0142]
[0143] It can be seen from the table that when no ethanol is added, the crystallization yield is low, and due to the high viscosity of the material, it is difficult to centrifuge and dry.
[0144] The various embodiments are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to in detail.
[0145] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A process for preparing D-tagatose crystals, characterized in that: The specific steps include: (1) adding a seed solution to a saturated D-tagatose solution under the assistance of ultrasound, and then growing the crystals at 50-60° C. to obtain a D-tagatose solution 1; wherein the growing the crystals is carried out by adding materials while evaporating and concentrating; (2) adding hydroxypropyl methylcellulose to the D-tagatose solution 1 obtained in step (1), and cooling and crystallizing the solution under infrared spectroscopy to obtain D-tagatose solution 2; (3) filtering the D-tagatose solution 2 obtained in step (2) to obtain a first filter residue and a filtrate, adding ethanol to the filtrate to continue crystallization, and then centrifuging to obtain a second filter residue, wherein the first filter residue and the second filter residue are D-tagatose crystals; The method for preparing the saturated D-tagatose solution in step (1) is as follows: adding an antioxidant to the D-tagatose solution and evaporating and concentrating the solution to a saturated solution, wherein the antioxidant is at least one of ascorbyl palmitate and tocopherol polyethylene glycol succinate; The seed solution in step (1) is a seed ethanol solution, and the seed solution is added by introducing compressed gas from the bottom; The steam pressure of the evaporation in step (1) is 150-200 kPa, the rate of the material addition is 0.2-0.5 L / h, and the material is a D-tagatose solution with a concentration of 50-60%; The cooling in step (2) is to 15-20°C, and the cooling rate is: 0.3-0.5°C per hour in the range of 60-55°C; 0.5-0.8°C per hour in the range of 55-40°C; 0.8-1.0°C per hour in the range of 40-25°C; 1.0-1.2°C per hour in the range of 25-15°C.
2. A process for preparing D-tagatose crystals according to claim 1, characterized in that: The concentration of the D-tagatose solution is 50-60% and the purity is 88-95%; The added amount of the antioxidant is 0.01-0.05% of the mass of the D-tagatose solution.
3. A process for preparing D-tagatose crystals according to claim 1, characterized in that: The power of the ultrasonic wave in step (1) is 100-150W; The mass ratio of the seed crystal to anhydrous ethanol in the seed crystal solution is 1:1-2, and the seed crystal is 100-150 mesh; The amount of seed crystal added is 1-3% of the mass of D-tagatose; The crystal growing time is 10-14h, and the stirring rate is 150-300rpm; The temperature of the saturated D-tagatose solution is 50-60°C.
4. A process for preparing D-tagatose crystals according to claim 1, characterized in that: The stirring rate of the saturated D-tagatose solution in step (1) is 400-500 rpm; Wherein, the compressed gas is any one of air, carbon dioxide, nitrogen, helium and argon; The pressure of the compressed gas is 0.3-1.2 MPa.
5. A process for preparing D-tagatose crystals according to claim 1, characterized in that: The amount of hydroxypropyl methylcellulose added in step (2) is 0.05-0.2% of the mass of the D-tagatose solution 1; The specific process of using the infrared spectrum is as follows: when the infrared spectrum absorption peak is 1020cm -1 The concentration change of D-tagatose was tracked, and the infrared spectrum was continuously collected every 23 seconds. The supersaturation was 1.05-1.20, and the supersaturation was controlled by controlling the temperature of cooling water. The temperature difference between the cooling water and the sugar solution was 3-5°C.
6. A process for preparing D-tagatose crystals according to claim 1, characterized in that: The filtration in step (3) uses a screen with a mesh size of 40-60.
7. A process for preparing D-tagatose crystals according to claim 1, characterized in that: In step (3), the amount of ethanol added is 3-5 times the volume of the filtrate, the flow acceleration is 0.1-0.2 L / h, and the crystallization time is 1-2 h; The stirring rate of the crystallization is 100-300 rpm.
Citation Information
Patent Citations
Crystallization method of D-tagatose
CN116444587A
High purity crystalline D-tagatose, compositions comprising same, and methods of preparation and use
CN116789718A